Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.5194/gchron-2020-28
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short communication: Driftwood provides reliable chronological markers in Arctic coastal deposits

Abstract: Abstract. Originating from the boreal forest and often transported over large distances, driftwood characterises many Arctic coastlines. Here we present a combined assessment of radiocarbon (14C) and dendrochronological (ring width) age estimates of driftwood samples to constrain the progradation of two Holocene beach-ridge systems near the Lena Delta in the Siberian Arctic (Laptev Sea). Our data show that the 14C ages obtained on syndepositional driftwood from beach deposits yield surprisingly coherent chrono… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…All rights reserved. ridge systems in coastal eastern Siberia (Sander et al, 2021), thus supporting the validity of age indications obtained from driftwood found on Holocene beaches. The aim of this paper is to utilise Arctic driftwood collected from modern shorelines to create a proxy-based reconstruction of regional sea ice conditions and Arctic Ocean circulation dynamics at a decadal resolution, and to evaluate inferences made from naturally felled driftwood material against the observational record.…”
Section: Accepted Articlesupporting
confidence: 83%
“…All rights reserved. ridge systems in coastal eastern Siberia (Sander et al, 2021), thus supporting the validity of age indications obtained from driftwood found on Holocene beaches. The aim of this paper is to utilise Arctic driftwood collected from modern shorelines to create a proxy-based reconstruction of regional sea ice conditions and Arctic Ocean circulation dynamics at a decadal resolution, and to evaluate inferences made from naturally felled driftwood material against the observational record.…”
Section: Accepted Articlesupporting
confidence: 83%
“…Sampling was mainly of old driftwood because the probability of successful cross-dating increases the greater the number of tree rings. Our new driftwood sampling sites from 2022 (red dots), together with the location of previous driftwood sampling sites (yellow dots), from which the age and origin of Arctic driftwood have been documented (Giddings 1940(Giddings , 1952Oswalt 1951, Stone 1958, Bartholin and Hjort 1987, Eggertsson 1993, 1994a, 1994bEggertsson and Laeyendecker 1995, Johansen 1998, 1999, 2001Nash 2000, Johansen and Hytteborn 2001, Hellmann et al 2013, 2016a, 2016bSteelandt et al 2015, Sander et al 2021, Shumilov et al 2020, Hole et al 2021, Linderholm et al 2021, Kolář et al 2022. The orange ovals refer to the main boreal source regions of Arctic driftwood along the Yenisei and Lena in central and eastern Siberia.…”
Section: Methodsmentioning
confidence: 99%
“…However, recent studies have highlighted that such assumptions can be incorrect, and a far wider extent of circumpolar sites must be considered during such processes, to accurately capture the potential history of samples (Hellmann et al, 2013). A recent combined assessment of radiocarbon and dendrochronological age estimates of Arctic driftwood samples found that radiocarbon dates from buried driftwood were in agreement with dendrochronological dating of modern beach ridge systems in coastal eastern Siberia (Sander et al, 2021), thus supporting the validity of age indications obtained from driftwood found on Holocene beaches.…”
Section: Using Driftwood To Infer Past Sea Ice Conditionsmentioning
confidence: 99%